Etude dynamique linéaire et non linéaire d’une poutre couplée avec un fluide - Sigrist, Jean-François; Lainé, Christian; Peseux, Bernard (European Journal of Computational Mechanics, 2006)
This paper deals with dynamic study of an elastic beam coupled to an incompressible fluid with free surface. To begin with, a modal analysis of the coupled fluidstructure problem by finite element coupling is carried out. Fluid-structure interaction effects are highlighted. Then, a dynamic analysis is performed, using a non-linear model in which the geometric non-linearity due to the axial force generated by stretching of the middle surface is taken into account. The coupled fluid-structure system is subjected to an imposed transverse acceleration. The problem is solved with a finite element method with a non-linear implicit scheme, the fluid effects are taken into account with an added mass operator which is discretised with a finite element technique. A numerical study is then carried out and shows the effect of geometrical non linearity as the imposed acceleration amplitude is increased. A comparison of non-linear behavior with fluid coupling is then investigated.